Entrepreneurial Finance: A Review of the Domain - Maleki, Ali (Journal of Entrepreneurship, Business and Economics, 2015)
Entrepreneurial finance is the study of value and resource allocation, applied to new ventures. This could be done in several ways, and each way includes several points to be taken into account. This paper tries to scrutinize the existing techniques and to investigate entrepreneurial financial planning. Finally, the paper concludes with some concluding remarks to extend the domain. Conceptual paper Reference to this paper should be made as follows: Maleki, A. (2015). “Entrepreneurial Finance: A Review of the Domain”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 2, pp. 110–120